International Student Migration: Did Brexit Close the Door to EU Students? - Joanna Clifton-Sprigg; Ines Homburg; Anneleen Huyghe; Suncica Vujic (Institute of Labor Economics (IZA), 2025)
This paper examines the effect of the Brexit process on international student migration from the European Union (EU) to the United Kingdom (UK). Using administrative data on higher education students in the UK, we employ a dynamic and a synthetic difference-in-differences estimator to compare EU to non-EU students. We show that the Brexit referendum itself and the introduction of visa requirements did not affect EU student migration. However, the introduction of higher tuition fees led to a large reduction in EU student applications to UK universities and colleges, and, subsequently, a decline in place offers, student acceptances, and enrolments. The effect ranges from 48% to 64%. Our findings suggest that increased tuition fees acted as a deterrent for EU students wanting to study in the UK.
Keywords: J61; C21; O15; I28; 330; Brexit; European Union; international student mobility; synthetic difference-in-differences; United Kingdom; higher education